Divisional ambiguity resolution for long range reference stations in network RTK. Issue 343 (July 2015) - Deng, J.; Wang, S. L.
Abstract : Increasing the distance between reference stations of network RTK can improve the flexibility of the reference stations sitting, reduce the number of reference stations and cut down construction and maintenance costs. However, it also decreases the correlation of spatial error and affects the real time performance and effectiveness of the network RTK positioning. Thus, the key techniques of long range network RTK need to be further optimised. Ambiguity resolution between reference stations is one of the most critical techniques. In this paper a divisional ambiguity resolution for long range reference stations of network RTK is proposed, so as to deal with the long fixed time and low success rate, especially for low elevation satellites. Based on conventional two-step ambiguity resolution, firstly, this new method calculates the wide-lane ambiguity by building M-W combination of pseudo-range and carrier observations. Second, the conventional ambiguity resolution as a whole is changed and satellites are divided into high elevation ones and low elevation ones, then the integer ambiguity of high elevation satellites is resolved by means of ionosphere-free combination with the relative zenith wet delay as a parameter. Finally, the Kalman filter model is established by the observation equation of high elevation satellites with calculated ambiguity and low elevation satellites, assisting to obtain the ambiguity of low elevation satellites quickly. The example selects a 196 km long baseline for comparative analysis. Result shows that it takes 733 s to resolve the ambiguity of all satellites by conventional ambiguity resolution in whole, and 252 s by divisional ambiguity resolution proposed in this paper. The new method saves about two thirds of resolution time, and also greatly improves the efficiency of ambiguity resolution of low elevation satellites for long baseline.